Invisible Trade Barriers: Trade Effects of US Antidumping Actions Against the People's Republic of China - Minsoo Lee; Donghyun Park; Aibo Cui (Asian Development Bank (ADB), 2013)
We conduct an empirical analysis on the impact of the United States (US) antidumping actions against the People's Republic of China (PRC) on the bilateral trade and US imports from other trade partners. Using the data set based on the Harmonized System (HS) tariff code, we examine the trade patterns of the PRC and other countries, and find evidence for the trade restriction effect and the trade diversion effect. Further, we examine the intensity and duration of both restriction and diversion effects. The antidumping measures have effectively raised the prices of imports from the PRC and reduced US imports from the PRC only in the short term. Nevertheless, due to the coexistence of trade diversion effects, the overall remedy effect of antidumping actions on domestic industries is considerably limited. In addition, we investigate other factors that influence the efficiency of antidumping measures, such as the antidumping duty amount, the PRC's market position in the US, and the US market share in the PRC.
hdl:11540/2064
Keywords: F12; F13; F14; 330; antidumping duty; trade diversion effect; trade restriction effect; the PRC